MANFAAT MUSIK LO-FI UNTUK MEMBANTU RELAKSASI BELAJAR - Fredrik Pridatirta; Paulina Tjandrawibawa (Jurnal Vicidi, 2020)
Music can be one tool to decide a person's atmosphere. Every music created has its own emitted emotional energy, and has a strong influence on human psychology, this provides evidence that music is related to emotions and moods in humans. The function of music also greatly influences learning activities. Like fashion trends where the trends of the era of the 80s to 90s were popular again at this time, the genre of music of the same era was also popular again. Lo-Fi music is not a genre but an ancient audio technology. In addition to its role as entertainment, lo-fi is also good for health because it can calm the mind and cut anxiety. This research was conducted to make a single lo-fi for students to help their learning process Keyword : Music, Lo-fi, Study method